2018
DOI: 10.1158/1541-7786.mcr-17-0680
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment-Derived Regulation of HIF Signaling Drives Transcriptional Heterogeneity in Glioblastoma Multiforme

Abstract: The evolving and highly heterogeneous nature of malignant brain tumors underlies their limited response to therapy and poor prognosis. In addition to genetic alterations, highly dynamic processes, such as transcriptional and metabolic reprogramming, play an important role in the development of tumor heterogeneity. The current study reports an adaptive mechanism in which the metabolic environment of malignant glioma drives transcriptional reprogramming. Multiregional analysis of a glioblastoma patient biopsy re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Astrocytes (CRL-8621), Tumor cell lines (Glioma Stem-like Cells, GSC 1, 2, and 3, purified from surgical specimens) and microglia cells (T0251) were cultured in serum-free conditions as described previously 40 . For combining different cell types within a co-culture, we used fluorescence tagged cells and culture them under serum-free condition along a time period of 48 h. Cells were plated on laminin-coated dishes as described previously 40 . Validation of co-culture was done after 24 h and 48 h by fluorescence microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Astrocytes (CRL-8621), Tumor cell lines (Glioma Stem-like Cells, GSC 1, 2, and 3, purified from surgical specimens) and microglia cells (T0251) were cultured in serum-free conditions as described previously 40 . For combining different cell types within a co-culture, we used fluorescence tagged cells and culture them under serum-free condition along a time period of 48 h. Cells were plated on laminin-coated dishes as described previously 40 . Validation of co-culture was done after 24 h and 48 h by fluorescence microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…In our preceding investigations, we demonstrated that the reactive transformation of astrocytes in our co-culture cell model closely mimics in-vivo circumstances, thereby allowing us to further map alterations in tumor cells caused by astrocytic crosstalk. By extracting gene signatures from all known transcriptional subtypes of glioblastoma (mesenchymal (Mes), proneural (PN), and classical (CL) tumors) as previous published [17], we were able to detect a subtype-switch of the BTSC#168 (classification in recent publication PN/CL [18,19]) cell line towards the mesenchymal phenotype. However, our results also showed that genes of the classical signature were partially up-regulated through astrocytic co-culture (Figure 2d).…”
Section: Resultsmentioning
confidence: 99%
“…In a next step, we aimed to confirm our findings in cell culture models from one commercial (LN229) and two primary, patient-derived cell lines. To respect any possible effects of GBM subgroup properties, both primary cell lines were classified beforehand by RNA-sequencing analysis [22]. We noticed, that a baseline PD-L1 expression was only observable in the mesenchymal cell line.…”
Section: Discussionmentioning
confidence: 99%
“…For immunostaining, cells were cultivated on slides and fixed with 3% formaldehyde for 10 min at room temperature. Immunostaining was performed as recently published by our group [22]. A Fluoview FV10i confocal microscope from Olympus was used for fluorescence microscopy.…”
Section: Methodsmentioning
confidence: 99%